A bridging the gap: The imperative for a digital platform in community mental health services - Kusumawaty, Ira; Yunike, Yunike; Harmiyati, Lela (Science Midwifery, 2024)
Community mental health services face ongoing challenges including fragmented care, difficulties evaluating outcomes, barriers to standardized support and educational tools, and stigmatizing attitudes. Digital technologies hold promises to help address gaps, but currently lack integrated platforms connecting services. Objective: To review literature on digital mental health interventions and examine their implications for a proposed cross-service digital platform in community mental health. Methods: A literature search identified peer-reviewed studies published between 2022-2024 evaluating digital tools in community or related mental health contexts. Relevant findings were synthesized regarding standardized platforms, remote psychological therapies, digitally enabled peer support, and technologies for stigma reduction. Results: Research supports digital platforms can help standardize functions, collect uniform outcomes data, and facilitate continuous learning. Smartphone apps show the potential to deliver effective remote therapies when combined with clinician support. Preliminary studies demonstrate digital peer support may mitigate loneliness and social connection platforms can positively shape attitudes. Conclusions: A thoughtfully designed shared digital platform incorporating validated tools, networked services, peer connection and stigma-reduction technologies may address fragmentation and empower community mental health clients. However, further research validating models is still needed given existing gaps. Equity, privacy, change management and adaptability must also be considered in future development and testing.